2020
DOI: 10.1039/d0sm00839g
|View full text |Cite
|
Sign up to set email alerts
|

Strain localization and failure of disordered particle rafts with tunable ductility during tensile deformation

Abstract: Quasi-static tensile experiments were performed for a model disordered solid consisting of a two-dimensional raft of polydisperse floating granular particles with capillary attractions. The ductility is tuned by controlling the...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…[15][16][17] In the quasi-static regime, the ductile behavior of particle rafts shows a dependence on particle size at small strains. 18 However, the dependence of the failure morphology on the pulling speed was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In the quasi-static regime, the ductile behavior of particle rafts shows a dependence on particle size at small strains. 18 However, the dependence of the failure morphology on the pulling speed was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…Zuo et al 22 innovatively examined the particle raft's behavior in quasi-static tensile and shear experiments, revealing the formation and evolution of the cracks. In use of a similar device, Xiao et al 23 found that small-particle rafts endured notable plastic deformation via long-distance capillary interactions. Moreover, To and Nage 24 witnessed particle rafts fragmenting into dispersed clusters along expanding fluid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, compressing the raft from two of its opposing ends at small strain can induce an instability in which the particles buckle out of the plane [6][7][8]. Likewise, pulling the raft from its opposing ends quasi-statically can induce ductile deformation [9]. The underlying fluid plays a crucial role.…”
Section: Introductionmentioning
confidence: 99%